Advances in Network-Based Information Systems The 20th International Conference on Network-Based Information Systems (NBiS-2017) - Barolli, Leonard; Enokido, Tomoya; Takizawa, Makoto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights the latest research findings, innovative research results, methods and development techniques from both theoretical and practical perspectives related to the emerging areas of information networking and their applications. It includes the Proceedings of the 20th International Conference on Network-Based Information Systems (NBiS-2017), held on August 24-26, 2017 in Toronto, Canada. Today's networks and information systems are evolving rapidly. Further, there are dynamic new trends and applications in information networking such as wireless sensor networks, ad hoc networks, peer-to-peer systems, vehicular networks, opportunistic networks, grid and cloud computing, pervasive and ubiquitous computing, multimedia systems, security, multi-agent systems, high-speed networks, and web-based systems. These networks are expected to manage the increasing number of users, provide support for a range of services, guarantee the quality of service (QoS), and optimize their network resources. In turn, these demands are the source of various research issues and challenges that have to be overcome - and which these Proceeding address. .
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence